Preparation method of waterproof impact-resistant fireproof cable

By forming a homemade waterproof layer and fireproof layer on the surface of the cable, combined with electrospinning, irradiation and aerogel protective layer technology, the problems of cables in rainwater erosion and fire are solved, and the effects of waterproof, fireproof and impact resistance are achieved.

CN119905301APending Publication Date: 2025-04-29胡星维
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411881459.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-28
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing cables are susceptible to rainwater erosion in sunshine and wind and rain, and the added flame retardant toxicity index is rising and it is expensive, making it difficult to meet market demand.

Method used

The homemade waterproof layer and fireproof layer are used to form silane hydroxide compound and zinc oxide layer by electrospinning and high-pressure mercury lamp irradiation. Diallyl diethoxysilane and graphene oxide are combined to form an aerogel protective layer, and the fireproof effect is enhanced by using aluminum sulfate and malonic acid reaction solution.

Benefits of technology

The waterproof and fire-proof effect of the cable is achieved, the impact resistance of the cable is improved, and the toxicity and cost of the flame retardant are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a waterproof impact-resistant fireproof cable, and relates to the technical field of cables. The preparation method comprises the following steps: firstly, forming a silane hydroxide compound by using 2-bromo-1, 5-hexadiene, trimethoxysilane and trioctylamine, and carrying out hydrolysis reaction on the silane hydroxide compound and infiltrated moisture to prevent moisture invasion; forming a first waterproof layer on the surface of the insulating layer by utilizing ultraviolet-assisted electrospinning; zinc nitrate water vapor is introduced to react with the first waterproof layer to obtain a second waterproof layer, so that the waterproof effect of the cable is enhanced; after the cable is coated with the shielding layer and the inner sheath layer, diallyldiethoxysilane and graphene are sequentially sprayed to form an aerogel protection layer, so that the cable has a fireproof effect; then aluminum sulfate is sprayed to form aluminum hydroxide to coat the surfaces of the pore channels of the aerogel, and then triethoxysilylbutyraldehyde and malonic acid are sequentially sprayed to be grafted to the surface of the aerogel, so that the fireproof effect of the cable is improved. The cable prepared by the invention has waterproof and fireproof effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cables, in particular to a method for preparing a waterproof, impact-resistant and fire-proof cable. Background Art

[0002] As we all know, with the rapid development of the national economy and the continuous upgrading of power facilities, the use of various types of wires and cables has increased significantly, driving a significant increase in the demand for various types of cable materials, and thus placing higher demands on the production cost and quality of cable materials. Polyvinyl chloride (PVC) offers advantages such as low cost, easy processing, excellent mechanical properties, corrosion resistance, and excellent insulation. When combined with linear low-density polyethylene (LLDPE) and polybutene-1, it possesses good plasticity and impact resistance. However, due to the flammability of plastic resins, fires can easily cause property damage and personal injury. Currently, both domestic and foreign manufacturers primarily add antimony trioxide or chlorinated paraffin as flame retardants, which increases the product's toxicity index. Furthermore, the price is very high, ranging from 180,000 to 250,000 yuan per ton, making it difficult for the market to accept.

[0003] In addition, cables are exposed to sunlight, wind and rain for a long time and are easily eroded by rainwater. Existing waterproofing methods mostly use pure paper-wrapped insulation glue radial waterproofing, which has poor waterproof performance and can easily cause cable corrosion and aging. Summary of the Invention

[0004] The object of the present invention is to provide a waterproof, impact-resistant and fire-resistant cable and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a waterproof, impact-resistant and fireproof cable, which includes a cable core, a self-made waterproof layer, a shielding layer, an inner sheath layer and a self-made fireproof layer.

[0006] Furthermore, the cable core includes a tinned copper wire core material and a cross-linked polyethylene insulation layer.

[0007] Furthermore, the self-made waterproof layer includes a first waterproof layer and a second waterproof layer; the first waterproof layer is prepared by the following method: N,N-dimethylformamide, tetrahydrofuran, and a silane hydroxide compound are mixed to obtain a spinning solution, which is electrospun toward a cable core, and then placed under a high-pressure mercury lamp for irradiation; the second waterproof layer is prepared by the following method: the cable core of the first waterproof layer is placed in a container, sealed, and zinc nitrate vapor is introduced to react for a period of time.

[0008] Furthermore, the silane hydroxide compound is prepared by the following method: 2-bromo-1,5-hexadiene, phenothiazine, chloroplatinic acid, isopropyl alcohol, and octamethylcyclotetrasiloxane are mixed, heated to a high temperature, and trimethoxysilane is added to react to obtain a silicon oxide compound; the silicon oxide compound and trioctyldecylamine are mixed, heated to react, petroleum ether is added, filtered, and then ethanol and ethyl acetate are added. After stirring for a period of time, the mixture is filtered and dried to obtain a quaternary ammonium compound, which is then exchanged with a strong base anion exchange resin.

[0009] Furthermore, the self-made fireproof layer is prepared by the following method: placing the inner sheath layer cable core under a high-pressure mercury lamp, spraying diallyldiethoxysilane, irradiating, heating, and then spraying graphene oxide solution. After reacting for a period of time, placing it in a water-alcohol vapor atmosphere, standing, and freeze-drying to obtain an aerogel cable core; coating the aerogel cable core with an aluminum sulfate solution of 0.2 to 0.4 times the mass of the aerogel cable core, reacting for a period of time, spraying sulfuric acid, ultrasonically treating, washing, drying, and then spraying malonic acid reaction liquid.

[0010] Furthermore, a method for preparing a waterproof, impact-resistant and fire-resistant cable comprises the following preparation steps: (1) N,N-dimethylformamide, tetrahydrofuran, and silane hydroxide compound are mixed in a mass ratio of 1:1:0.1 to 1:1:0.2, stirred and dissolved to obtain a spinning solution, and electrospun to a film thickness of 0.1 to 0.3 mm on the cable core. The film is then placed under a 2kW high-pressure mercury lamp at a distance of 200 mm and irradiated for 30 to 60 seconds to obtain a first waterproof layer cable core; (2) Place the first waterproof layer cable core in a container, seal it, and introduce 180°C zinc nitrate vapor at 20 mL / h. After reacting for 15-18 hours, take it out, cool it to room temperature, and dry it at 80°C for 7-10 hours to obtain the self-made waterproof layer cable core; (3) Using tinned copper wire to weave a shielding layer with a thickness of 0.1~0.3mm on the surface of the self-made waterproof layer cable core to obtain a shielding layer cable core; (4) Cross-linked polyethylene, polyvinyl chloride resin, linear low-density polyethylene, poly-1-butene, γ-aminopropyltriethoxysilane, silicon dioxide, antioxidant 264, calcium stearate, zinc stearate, and epoxy soybean oil were mixed in a mass ratio of 1:2:1:1.8:0.1:0.2:0.08:0.1:0.05:1, stirred at 100°C and 2000 rpm for 1-6 minutes, and then extruded an inner sheath layer onto the shielding layer cable core at 145-160°C to obtain an inner sheath layer cable core; (5) Place the inner sheath cable core under a 2kW high-pressure mercury lamp at a distance of 200mm, spray diallyldiethoxysilane at a concentration of 0.5 to 0.8 times the mass of the inner sheath cable core, irradiate for 44 to 58 seconds, heat to 60°C, spray graphene oxide solution at a concentration of 88 to 100 times the mass of the inner sheath cable core, and the mass ratio of graphene oxide, deionized water, and ascorbic acid in the graphene oxide solution is 1:200:0.1 to 1:500:0.5. After reacting for 7 to 10 hours, place it in a hydroalcohol vapor atmosphere, and the mass ratio of deionized water and anhydrous ethanol in the hydroalcohol vapor is 1:9. After standing for 10 to 13 hours, freeze it at -15°C for 4 to 7 hours to obtain an aerogel cable core. (6) Place the aerogel cable core in a container, spray it with aluminum sulfate solution at a concentration of 0.2 to 0.4 times the mass of the aerogel cable core, react at 160°C for 35 to 48 minutes, spray it with 8.9% sulfuric acid at a concentration of 0.01 to 0.03 times the mass of the aerogel cable core, ultrasonicate at 30kHz for 31 to 43 minutes, wash it with deionized water for 6 to 8 times, dry it at 100°C for 9 to 13 hours, spray it with malonic acid reaction solution at a concentration of 0.4 to 0.7 times the mass of the aerogel cable core, react it for 4.5 to 7 hours, wash it with deionized water for 6 to 8 times, and dry it at 60°C for 10 to 14 hours to obtain a waterproof, impact-resistant and fire-resistant cable.

[0011] Furthermore, the preparation method of the silane hydroxide compound in step (1) is: A. Mix 2-bromo-1,5-hexadiene, phenothiazine, chloroplatinic acid, isopropyl alcohol, and octamethylcyclotetrasiloxane in a mass ratio of 1:0.01:0.001:0.004:0.0006 to 1:0.02:0.002:0.006:0.0008, stir evenly, heat to 90-95°C, add trimethoxysilane (0.8-1.1 times the mass of 2-bromo-1,5-hexadiene), and react for 2-4.5 hours to obtain a silicon oxide compound; B. Mix the silicon oxide compound and trioctyldecylamine in a mass ratio of 1:1.5 to 1:2.0, heat to 78°C, react for 40 to 44 hours, add petroleum ether in an amount of 1.5 to 2.0 times the mass of the silicon oxide compound, stir evenly, filter with suction, then add ethanol in an amount of 2 to 4 times the mass of the silicon oxide compound and ethyl acetate in an amount of 1.1 to 2.3 times the mass of the silicon oxide compound, stir at 80 rpm for 15 to 24 minutes, filter with suction, and dry at 60°C for 4 to 7 hours to obtain a quaternary ammonium compound; C. Place a strong base anion exchange resin in an ion exchange column, add a quaternary ammonium compound solution with a mass ratio of 1.0 to 1.5 times that of the strong base anion exchange resin at 50 mL / h, and the mass ratio of the quaternary ammonium compound to anhydrous ethanol in the quaternary ammonium compound solution is 1:3. Then wash with anhydrous ethanol 2 to 4 times, rotary evaporate at 300 rpm and 80°C for 60 to 72 minutes, and then dry at 70°C for 3 to 6 hours.

[0012] Furthermore, the electrospinning conditions in step (1) are as follows: spinning voltage is 15 kV, spinning distance is 18 cm, spinning speed is 0.4 mL / h, both ends of the cable core are fixed, and the rotation speed is 60 rpm.

[0013] Furthermore, the zinc nitrate vapor in step (2) is prepared by mixing zinc nitrate hexahydrate and deionized water in a mass ratio of 1:13.4.

[0014] Furthermore, the preparation method of the aluminum sulfate solution in step (6) is: mixing aluminum sulfate and deionized water in a mass ratio of 1:2.6, and adding sodium hydroxide until the solution pH is 9-10; the preparation method of the malonic acid reaction solution is: mixing triethoxysilylbutyraldehyde, malonic acid, N,N-dimethylformamide, and pyridine in a mass ratio of 1:1.1:3:0.2-1:1.6:5:0.4, heating to 90°C, reacting for 7-10 hours, cooling to room temperature, adding ice water 9-13 times the mass of triethoxysilylbutyraldehyde, and then adding hydrochloric acid until the solution pH is 1-2, filtering to obtain a filter cake, and then adding deionized water 2-4 times the mass of the filter cake.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention sequentially covers a self-made waterproof layer, a shielding layer, an inner sheath layer and a self-made fireproof layer on the surface of the cable core to achieve waterproof and flame retardant effects.

[0016] First, the present invention utilizes the double bond of 2-bromo-1,5-hexadiene to undergo an addition reaction with the silicon-hydrogen bond of trimethoxysilane, then the bromide ion undergoes a quaternization reaction with trioctyldecylamine, and then the hydroxylation is performed through a strong basic anion exchange resin to obtain a silane hydroxide compound, which can undergo a hydrolysis reaction with infiltrated water to eliminate internal water and fill the micropores in the water tree area to prevent water from invading again, making the cable waterproof. Electrospinning is used to form a first waterproof layer on the surface of the insulation layer, and ultraviolet irradiation is used during the electrospinning process to cause the remaining double bonds of the silane hydroxide compound to undergo a free radical reaction with the cross-linked polyethylene insulation layer, so that the first waterproof layer and the insulation layer are tightly cross-linked to prevent water molecules from penetrating, and at the same time, long hydrophobic chains are introduced into the surface to enhance the waterproofness of the cable. Then, zinc nitrate water vapor is introduced, and the zinc ions react with the hydroxide ions of the first waterproof layer and are deposited on the surface of the first waterproof layer. Zinc oxide is formed through thermal oxidation, and gradually grows and accumulates to form a second waterproof layer with an onion-like structure. The first and second waterproof layers are tightly cross-linked, which is beneficial to improving the waterproof effect of the cable.

[0017] Secondly, the present invention performs a first spraying, supplemented by ultraviolet irradiation, to cause diallyldiethoxysilane and the cross-linked polyethylene of the inner sheath layer to undergo free radical polymerization; then a second spraying is performed, and graphene is deposited on the surface of the inner sheath layer by utilizing the silicon-oxygen bond of diallyldiethoxysilane, and is hydrothermally reduced to form an aerogel protective layer, which slows down the spread of flames, isolates heat, and makes the cable have a fireproof effect; then a third spraying is performed, and aluminum sulfate is adsorbed by capillary action, and is hydrolyzed to form aluminum hydroxide coated on the surface of the aerogel pores, and during the coating process, the hydroxyl groups on the surface of the graphene can react with the aluminum hydroxide to form a bond, so that the aluminum hydroxide is firmly fixed in the aerogel, decomposes under heat to absorb a large amount of heat, reduces the flame temperature, and at the same time, the decomposition products fill the pores of the aerogel, isolate oxygen, and enhance the fireproof effect of the cable; then, a fourth spraying is performed, and triethoxysilylbutyraldehyde and malonic acid undergo a condensation reaction, and are then grafted to the aerogel surface by utilizing silicon-oxygen bonds, vaporized under high temperature conditions, dilute the oxygen concentration in the air, and enhance the fireproof effect of the cable. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0019] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the waterproof, impact-resistant and fire-resistant cables prepared in the following examples. Waterproofness: Cable samples of the embodiment and the comparative example with the same length and size were taken for waterproofing effect test. The cable samples were immersed in 40°C tap water and the rate of change of the dielectric constant was measured after immersion for 7 days.

[0020] Fire resistance: Cable samples of the embodiment and the comparative example with the same length and size were taken for fire resistance test, referring to GB12666.6, and the continuous power supply time of the cables under the high temperature of 1000°C flame was measured.

[0021] Example 1 (1) 2-bromo-1,5-hexadiene, phenothiazine, chloroplatinic acid, isopropyl alcohol, and octamethylcyclotetrasiloxane were mixed in a mass ratio of 1:0.01:0.001:0.004:0.0006, stirred evenly, and then heated to 90°C. Trimethoxysilane (0.8 times the mass of 2-bromo-1,5-hexadiene) was added and reacted for 2 hours to obtain a silicon oxide compound. (2) Mix the silicon oxide compound and trioctyldecylamine in a mass ratio of 1:1.5, heat to 78°C, react for 40 hours, add petroleum ether 1.5 times the mass of the silicon oxide compound, stir evenly, filter, then add ethanol 2 times the mass of the silicon oxide compound and ethyl acetate 1.1 times the mass of the silicon oxide compound, stir at 80 rpm for 15 minutes, filter, and dry at 60°C for 4 hours to obtain a quaternary ammonium compound; (3) placing a strong base anion exchange resin in an ion exchange column, adding a quaternary ammonium compound solution of 1 times the mass of the strong base anion exchange resin at 50 mL / h, wherein the mass ratio of the quaternary ammonium compound to anhydrous ethanol in the quaternary ammonium compound solution is 1:3, and then washing with anhydrous ethanol twice, rotary evaporating at 300 rpm and 80°C for 60 min, and drying at 70°C for 3 h to obtain a silane hydroxide compound; (4) N,N-dimethylformamide, tetrahydrofuran, and silane hydroxide compound were mixed in a mass ratio of 1:1:0.1, stirred and dissolved to obtain a spinning solution, and electrospun to the cable core until the film thickness was 0.1 mm. The solution was then placed under a 2kW high-pressure mercury lamp at a distance of 200 mm and irradiated for 30 seconds to obtain a first waterproof layer cable core. The electrospinning conditions were as follows: spinning voltage of 15 kV, spinning distance of 18 cm, spinning speed of 0.4 mL / h, both ends of the cable core were fixed, and the rotation speed was 60 rpm. (5) Place the first waterproof layer cable core in a container, seal it, and introduce 180°C zinc nitrate vapor at 20 mL / h. The mass ratio of zinc nitrate hexahydrate to deionized water in the zinc nitrate vapor is 1:13.4. After reacting for 15 hours, take it out, cool it to room temperature, and dry it at 80°C for 7 hours to obtain a self-made waterproof layer cable core. (6) Using tinned copper wire, a shielding layer with a thickness of 0.1 mm is woven onto the surface of the self-made waterproof layer cable core to obtain a shielding layer cable core; (7) Cross-linked polyethylene, polyvinyl chloride resin, linear low-density polyethylene, poly-1-butene, γ-aminopropyltriethoxysilane, silicon dioxide, antioxidant 264, calcium stearate, zinc stearate, and epoxy soybean oil were mixed in a mass ratio of 1:2:1:1.8:0.1:0.2:0.08:0.1:0.05:1, stirred at 100°C and 2000 rpm for 1 minute, and then extruded the inner sheath layer onto the shielding layer cable core at 145-160°C to obtain the inner sheath layer cable core; (8) Place the inner sheath cable core under a 2kW high-pressure mercury lamp at a distance of 200mm, spray diallyldiethoxysilane at a mass of 0.5 times the mass of the inner sheath cable core, irradiate for 44s, heat to 60℃, spray graphene oxide solution at a mass of 88 times the mass of the inner sheath cable core, the mass ratio of graphene oxide, deionized water, and ascorbic acid in the graphene oxide solution is 1:200:0.1, react for 7h, place in a hydroalcohol vapor atmosphere, the mass ratio of deionized water and anhydrous ethanol in the hydroalcohol vapor is 1:9, stand for 10h, and freeze at -15℃ for 4h to obtain an aerogel cable core; (9) Triethoxysilylbutyraldehyde, malonic acid, N,N-dimethylformamide, and pyridine were mixed in a mass ratio of 1:1.1:3:0.2, heated to 90°C, reacted for 7 hours, cooled to room temperature, and ice water 9 times the mass of triethoxysilylbutyraldehyde was added. Hydrochloric acid was then added until the pH of the solution was 1. Filtered to obtain a filter cake, and deionized water 2 times the mass of the filter cake was added to obtain a malonic acid reaction solution. (10) Aluminum sulfate and deionized water were mixed in a mass ratio of 1:2.6, and sodium hydroxide was added until the pH of the solution was 9 to obtain an aluminum sulfate solution; the aerogel cable core was placed in a container, and 0.2 times the mass of the aerogel cable core was sprayed with aluminum sulfate solution, reacted at 160°C for 35 minutes, and then 0.01 times the mass of the aerogel cable core was sprayed with 8.9% sulfuric acid, ultrasonicated at 30kHz for 31 minutes, washed with deionized water for 6 times, dried at 100°C for 9 hours, and then sprayed with 0.4 times the mass of the aerogel cable core with malonic acid reaction solution, reacted for 4.5 hours, washed with deionized water for 6 times, and dried at 60°C for 10 hours to obtain a waterproof, impact-resistant and fire-resistant cable.

[0022] Example 2 (1) 2-bromo-1,5-hexadiene, phenothiazine, chloroplatinic acid, isopropyl alcohol, and octamethylcyclotetrasiloxane were mixed in a mass ratio of 1:0.015:0.0015:0.005:0.0007, stirred evenly, and then heated to 92°C. Trimethoxysilane (0.95 times the mass of 2-bromo-1,5-hexadiene) was added and reacted for 3.3 hours to obtain a silicon oxide compound. (2) The silicon oxide compound and trioctyldecylamine were mixed in a mass ratio of 1:1.8, heated to 78°C, reacted for 42 hours, and then 1.8 times the mass of petroleum ether of the silicon oxide compound was added. After stirring evenly, the mixture was filtered. Then, 3 times the mass of ethanol and 1.7 times the mass of ethyl acetate of the silicon oxide compound were added. The mixture was stirred at 80 rpm for 19 minutes, filtered, and dried at 60°C for 5.5 hours to obtain a quaternary ammonium compound. (3) placing a strong base anion exchange resin in an ion exchange column, adding a quaternary ammonium compound solution of 1.25 times the mass of the strong base anion exchange resin at 50 mL / h, wherein the mass ratio of the quaternary ammonium compound to anhydrous ethanol in the quaternary ammonium compound solution is 1:3, and then washing with anhydrous ethanol for 3 times, rotary evaporating at 300 rpm and 80°C for 66 min, and drying at 70°C for 4.5 h to obtain a silane hydroxide compound; (4) N,N-dimethylformamide, tetrahydrofuran, and silane hydroxide compound were mixed in a mass ratio of 1:1:0.15, stirred and dissolved to obtain a spinning solution, and electrospun to a cable core until the film thickness was 0.2 mm. The solution was then placed under a 2kW high-pressure mercury lamp at a distance of 200 mm and irradiated for 45 seconds to obtain a first waterproof layer cable core. The electrospinning conditions were as follows: spinning voltage of 15 kV, spinning distance of 18 cm, spinning speed of 0.4 mL / h, both ends of the cable core were fixed, and the rotation speed was 60 rpm. (5) Place the first waterproof layer cable core in a container, seal it, and introduce 180°C zinc nitrate vapor at a rate of 20 mL / h. The mass ratio of zinc nitrate hexahydrate to deionized water in the zinc nitrate vapor is 1:13.4. After reacting for 16.5 hours, take it out, cool it to room temperature, and dry it at 80°C for 8.5 hours to obtain a self-made waterproof layer cable core. (6) Using tinned copper wire, a shielding layer with a thickness of 0.2 mm is woven onto the surface of the self-made waterproof layer cable core to obtain a shielding layer cable core; (7) Cross-linked polyethylene, polyvinyl chloride resin, linear low-density polyethylene, poly-1-butene, γ-aminopropyltriethoxysilane, silicon dioxide, antioxidant 264, calcium stearate, zinc stearate, and epoxy soybean oil were mixed in a mass ratio of 1:2:1:1.8:0.1:0.2:0.08:0.1:0.05:1, stirred at 100°C and 2000 rpm for 3 minutes, and then extruded the inner sheath layer onto the shielding layer cable core at 145-160°C to obtain the inner sheath layer cable core; (8) Place the inner sheath cable core under a 2kW high-pressure mercury lamp at a distance of 200mm, spray diallyldiethoxysilane at a mass of 0.65 times the mass of the inner sheath cable core, irradiate for 51s, heat to 60℃, spray graphene oxide solution at a mass of 94 times the mass of the inner sheath cable core, the mass ratio of graphene oxide, deionized water, and ascorbic acid in the graphene oxide solution is 1:350:0.3, react for 8.5h, place in a hydroalcohol vapor atmosphere, the mass ratio of deionized water and anhydrous ethanol in the hydroalcohol vapor is 1:9, stand for 11.5h, and freeze at -15℃ for 5.5h to obtain an aerogel cable core; (9) Triethoxysilylbutyraldehyde, malonic acid, N,N-dimethylformamide, and pyridine were mixed in a mass ratio of 1:1.4:4:0.3, heated to 90°C, reacted for 8.5 hours, cooled to room temperature, added with ice water 11 times the mass of triethoxysilylbutyraldehyde, and then added with hydrochloric acid until the pH of the solution was 1.5. Filtered to obtain a filter cake, and then added with deionized water 3 times the mass of the filter cake to obtain a malonic acid reaction solution; (10) Aluminum sulfate and deionized water were mixed in a mass ratio of 1:2.6, and sodium hydroxide was added until the pH of the solution was 9.5 to obtain an aluminum sulfate solution; the aerogel cable core was placed in a container, and 0.3 times the mass of the aerogel cable core was sprayed with aluminum sulfate solution, reacted at 160°C for 41 minutes, and then 0.02 times the mass of the aerogel cable core was sprayed with 8.9% sulfuric acid, ultrasonicated at 30kHz for 37 minutes, washed with deionized water for 7 times, dried at 100°C for 11 hours, and then sprayed with 0.55 times the mass of the aerogel cable core with malonic acid reaction solution, reacted for 5.8 hours, washed with deionized water for 7 times, and dried at 60°C for 12 hours to obtain a waterproof, impact-resistant and fire-resistant cable.

[0023] Example 3 (1) 2-bromo-1,5-hexadiene, phenothiazine, chloroplatinic acid, isopropyl alcohol, and octamethylcyclotetrasiloxane were mixed in a mass ratio of 1:0.02:0.002:0.006:0.0008, stirred evenly, and then heated to 95°C. Trimethoxysilane (1.1 times the mass of 2-bromo-1,5-hexadiene) was added and reacted for 4.5 hours to obtain a silicon oxide compound. (2) Mix the silicon oxide compound and trioctyldecylamine in a mass ratio of 1:2.0, heat to 78°C, react for 44 hours, add petroleum ether 2.0 times the mass of the silicon oxide compound, stir evenly, filter, then add ethanol 4 times the mass of the silicon oxide compound and ethyl acetate 2.3 times the mass of the silicon oxide compound, stir at 80 rpm for 24 minutes, filter, and dry at 60°C for 7 hours to obtain a quaternary ammonium compound; (3) placing a strong base anion exchange resin in an ion exchange column, adding a quaternary ammonium compound solution of 1.5 times the mass of the strong base anion exchange resin at 50 mL / h, wherein the mass ratio of the quaternary ammonium compound to anhydrous ethanol in the quaternary ammonium compound solution is 1:3, and then washing with anhydrous ethanol for 4 times, rotary evaporating at 300 rpm and 80°C for 72 min, and drying at 70°C for 6 h to obtain a silane hydroxide compound; (4) N,N-dimethylformamide, tetrahydrofuran, and silane hydroxide compound were mixed in a mass ratio of 1:1:0.2, stirred and dissolved to obtain a spinning solution, and electrospun to the cable core until the film thickness was 0.3 mm. The solution was then placed under a 2kW high-pressure mercury lamp at a distance of 200 mm and irradiated for 60 seconds to obtain a first waterproof layer cable core. The electrospinning conditions were as follows: spinning voltage of 15 kV, spinning distance of 18 cm, spinning speed of 0.4 mL / h, both ends of the cable core were fixed, and the rotation speed was 60 rpm. (5) Place the first waterproof layer cable core in a container, seal it, and introduce 180°C zinc nitrate vapor at 20 mL / h. The mass ratio of zinc nitrate hexahydrate to deionized water in the zinc nitrate vapor is 1:13.4. After reacting for 18 hours, take it out, cool it to room temperature, and dry it at 80°C for 10 hours to obtain the self-made waterproof layer cable core; (6) Using tinned copper wire, a shielding layer with a thickness of 0.3 mm is woven onto the surface of the self-made waterproof layer cable core to obtain a shielding layer cable core; (7) Cross-linked polyethylene, polyvinyl chloride resin, linear low-density polyethylene, poly-1-butene, γ-aminopropyltriethoxysilane, silicon dioxide, antioxidant 264, calcium stearate, zinc stearate, and epoxy soybean oil were mixed in a mass ratio of 1:2:1:1.8:0.1:0.2:0.08:0.1:0.05:1, stirred at 100°C and 2000 rpm for 6 minutes, and then extruded the inner sheath layer onto the shielding layer cable core at 145-160°C to obtain the inner sheath layer cable core; (8) Place the inner sheath cable core under a 2kW high-pressure mercury lamp at a distance of 200mm, spray diallyldiethoxysilane at a concentration of 0.8 times the mass of the inner sheath cable core, irradiate for 58s, heat to 60°C, spray graphene oxide solution at a concentration of 100 times the mass of the inner sheath cable core, and the mass ratio of graphene oxide, deionized water, and ascorbic acid in the graphene oxide solution is 1:500:0.5. After reacting for 7-10h, place it in a hydroalcohol vapor atmosphere, and the mass ratio of deionized water and anhydrous ethanol in the hydroalcohol vapor is 1:9. After standing for 13h, freeze it at -15°C for 7h to obtain an aerogel cable core. (9) Triethoxysilylbutyraldehyde, malonic acid, N,N-dimethylformamide, and pyridine were mixed in a mass ratio of 1:1.6:5:0.4, heated to 90°C, reacted for 10 hours, cooled to room temperature, and ice water 13 times the mass of triethoxysilylbutyraldehyde was added. Hydrochloric acid was then added until the pH of the solution was 2. Filtered to obtain a filter cake, and deionized water 4 times the mass of the filter cake was added to obtain a malonic acid reaction solution. (10) Aluminum sulfate and deionized water were mixed in a mass ratio of 1:2.6, and sodium hydroxide was added until the pH of the solution was 10 to obtain an aluminum sulfate solution. The aerogel cable core was placed in a container and sprayed with 0.4 times the mass of the aerogel cable core aluminum sulfate solution. After reacting at 160 ° C for 48 minutes, 0.03 times the mass of the aerogel cable core was sprayed with 8.9% sulfuric acid. After 30kHz ultrasound for 43 minutes, the aerogel cable core was washed with deionized water for 8 times, dried at 100 ° C for 13 hours, and 0.7 times the mass of the aerogel cable core malonic acid reaction solution was sprayed. The reaction was continued for 7 hours, washed with deionized water for 8 times, and dried at 60 ° C for 14 hours to obtain a waterproof, impact-resistant and fire-resistant cable.

[0024] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that step (1) is omitted, and step (2) is changed to: trimethoxysilane and trioctyldecylamine are mixed in a mass ratio of 1:1.8, heated to 78°C, reacted for 42 hours, and then 1.8 times the mass of petroleum ether of the trimethoxysilane is added. After stirring evenly, the mixture is filtered with suction. Then, 3 times the mass of ethanol and 1.7 times the mass of ethyl acetate of the trimethoxysilane are added. The mixture is stirred at 80 rpm for 19 minutes, filtered with suction, and dried at 60°C for 5.5 hours to obtain a quaternary ammonium compound. The remaining steps are the same as those in Example 2.

[0025] Comparative Example 2 Comparative Example 2 differs from Example 2 in that step (3) is omitted, and step (4) is modified as follows: N,N-dimethylformamide, tetrahydrofuran, and a quaternary ammonium compound are mixed in a mass ratio of 1:1:0.15, stirred and dissolved to obtain a spinning solution, and electrospun onto a cable core until the film thickness is 0.2 mm. The solution is then placed under a 2 kW high-pressure mercury lamp at a distance of 200 mm and irradiated for 45 seconds to obtain a first waterproof layer cable core; the electrospinning conditions are as follows: a spinning voltage of 15 kV, a spinning distance of 18 cm, a spinning speed of 0.4 mL / h, fixed at both ends of the cable core, and a rotation speed of 60 rpm. The remaining steps are the same as in Example 2.

[0026] Comparative Example 3 The difference between Comparative Example 3 and Example 2 lies in the difference in step (8). Step (8) is changed to: placing the inner sheath layer cable core in a container, heating it to 60°C, spraying a graphene oxide solution 94 times the mass of the inner sheath layer cable core, wherein the mass ratio of graphene oxide, deionized water, and ascorbic acid in the graphene oxide solution is 1:350:0.3, reacting for 8.5 hours, placing it in a hydroalcohol vapor atmosphere, wherein the mass ratio of deionized water and anhydrous ethanol in the hydroalcohol vapor is 1:9, standing it for 11.5 hours, and freezing it at -15°C for 5.5 hours to obtain the aerogel cable core. The remaining steps are the same as those in Example 2.

[0027] Comparative Example 4 The difference between Comparative Example 4 and Example 2 lies in step (8), which is modified as follows: the inner sheath layer cable core is placed under a 2kW high-pressure mercury lamp at a distance of 200mm, and 0.65 times the mass of the inner sheath layer cable core is sprayed with diallyldiethoxysilane, and irradiated for 51s to obtain an aerogel cable core. The remaining steps are the same as those in Example 2.

[0028] Comparative Example 5 The difference between Comparative Example 5 and Example 2 lies in step (10). Step (10) is modified as follows: placing the aerogel cable core in a container, spraying 0.55 times the mass of the aerogel cable core with a malonic acid reaction solution, reacting for 5.8 hours, washing with deionized water seven times, and drying at 60°C for 12 hours to obtain a waterproof, impact-resistant, fire-resistant cable. The remaining steps are the same as those in Example 2.

[0029] Comparative Example 6 Comparative Example 6 differs from Example 2 in that step (9) is omitted and step (10) is modified as follows: aluminum sulfate and deionized water are mixed in a mass ratio of 1:2.6, sodium hydroxide is added until the pH of the solution reaches 9.5, and an aluminum sulfate solution is obtained; the aerogel cable core is placed in a container, and the aluminum sulfate solution is sprayed at a volume of 0.3 times the mass of the aerogel cable core. After reacting at 160° C. for 41 minutes, sulfuric acid with a mass fraction of 8.9% is sprayed at a volume of 0.02 times the mass of the aerogel cable core. After ultrasonication at 30 kHz for 37 minutes, the cable is washed with deionized water seven times and dried at 100° C. for 11 hours to obtain a waterproof, impact-resistant, and fire-resistant cable. The remaining steps are the same as those in Example 2.

[0030] Effect Examples Table 1 below shows the performance analysis results of the waterproof, impact-resistant and fire-resistant cables of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0031] Table 1 From the comparison of the experimental data of the continuous power supply time of the embodiment and the comparative example, it can be found that the present invention uses diallyldiethoxysilane to firmly fix the graphene on the surface of the inner sheath layer, and forms an aerogel protective layer through hydrothermal reduction, which slows down the spread of flames, isolates heat, and makes the cable have a fireproof effect; sprays and absorbs aluminum sulfate, uses the capillary effect to fill the aerogel pores, and then forms aluminum hydroxide to coat the surface of the aerogel pores, and produces a bonding effect, which reduces the flame temperature and isolates oxygen at the same time, thereby enhancing the fireproof effect of the cable; then, triethoxysilylbutyraldehyde and malonic acid are grafted on the surface of the aerogel, and when Fire is vaporized first, diluting the oxygen concentration in the air and enhancing the fireproof effect of the cable. Comparison of the experimental data of the dielectric constant change rate between the embodiment and the comparative example shows that the present invention utilizes 2-bromo-1,5-hexadiene, trimethoxysilane and trioctyldecylamine to form a silane hydroxide compound, which can undergo a hydrolysis reaction with the infiltrated moisture to eliminate the internal moisture. Ultraviolet irradiation-electrospinning is utilized to tightly cross-link the surface of the insulating layer to form a first waterproof layer. Zinc nitrate vapor is then introduced to react with the first waterproof layer to form zinc oxide, forming a second waterproof layer with an onion-like structure, which is beneficial to improving the waterproof effect of the cable.

[0032] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be encompassed therein. Any reference in a claim should not be construed as limiting the claim to which it relates.

Claims

1. A method for preparing a waterproof, impact-resistant and fire-resistant cable, characterized in that: The method comprises the following preparation steps: (1) 2-bromo-1,5-hexadiene, phenothiazine, chloroplatinic acid, isopropanol and octamethylcyclotetrasiloxane were mixed in a mass ratio of 1:0.02:0.002:0.006:0.0008, stirred evenly, heated to 95°C, and trimethoxysilane (1.1 times the mass of 2-bromo-1,5-hexadiene) was added, and reacted for 4.5 hours to obtain a silicon oxide compound; (2) Mix the silicon oxide compound and trioctyldecylamine in a mass ratio of 1:2.0, heat to 78°C, react for 44 hours, add petroleum ether 2.0 times the mass of the silicon oxide compound, stir evenly, filter, then add ethanol 4 times the mass of the silicon oxide compound and ethyl acetate 2.3 times the mass of the silicon oxide compound, stir at 80 rpm for 24 minutes, filter, and dry at 60°C for 7 hours to obtain a quaternary ammonium compound; (3) placing a strong base anion exchange resin in an ion exchange column, adding a quaternary ammonium compound solution of 1.5 times the mass of the strong base anion exchange resin at 50 mL / h, wherein the mass ratio of the quaternary ammonium compound to anhydrous ethanol in the quaternary ammonium compound solution is 1:3, then washing with anhydrous ethanol for 4 times, rotary evaporating at 300 rpm and 80° C. for 72 min, and drying at 70° C. for 6 h to obtain a silane hydroxide compound; (4) N,N-dimethylformamide, tetrahydrofuran and silane hydroxide compound were mixed in a mass ratio of 1:1:0.2, stirred and dissolved to obtain a spinning solution, and electrospun to the cable core until the film thickness was 0.3 mm, and then placed under a 2kW high-pressure mercury lamp at a distance of 200 mm for 60 seconds to obtain a first waterproof layer cable core; the electrospinning conditions were: spinning voltage of 15 kV, spinning distance of 18 cm, spinning speed of 0.4 mL / h, both ends of the cable core were fixed, and the rotation speed was 60 rpm; (5) The first waterproof layer cable core is placed in a container, sealed, and 180°C zinc nitrate vapor is introduced at 20 mL / h, where the mass ratio of zinc nitrate hexahydrate to deionized water in the zinc nitrate vapor is 1:13.

4. After reacting for 18 hours, the cable core is taken out, cooled to room temperature, and dried at 80°C for 10 hours to obtain a self-made waterproof layer cable core; (6) Using tinned copper wire, a shielding layer with a thickness of 0.3 mm is woven onto the surface of the self-made waterproof layer cable core to obtain a shielding layer cable core; (7) Cross-linked polyethylene, polyvinyl chloride resin, linear low-density polyethylene, poly-1-butene, γ-aminopropyltriethoxysilane, silicon dioxide, antioxidant 264, calcium stearate, zinc stearate, and epoxy soybean oil were mixed in a mass ratio of 1:2:1:1.8:0.1:0.2:0.08:0.1:0.05:1, stirred at 100°C and 2000 rpm for 6 minutes, and then extruded an inner sheath layer onto the shielding layer cable core at 145-160°C to obtain an inner sheath layer cable core; (8) Place the inner sheath cable core under a 2kW high-pressure mercury lamp at a distance of 200mm, spray 0.8 times the mass of the inner sheath cable core with diallyldiethoxysilane, irradiate for 58s, heat to 60°C, spray 100 times the mass of the inner sheath cable core with graphene oxide solution, the mass ratio of graphene oxide, deionized water, and ascorbic acid in the graphene oxide solution is 1:500:0.5, react for 7-10h, place in a water-alcohol vapor atmosphere, the mass ratio of deionized water and anhydrous ethanol in the water-alcohol vapor is 1:9, stand for 13h, and freeze at -15°C for 7h to obtain an aerogel cable core; (9) Triethoxysilylbutyraldehyde, malonic acid, N,N-dimethylformamide, and pyridine were mixed in a mass ratio of 1:1.6:5:0.4, heated to 90°C, reacted for 10 hours, cooled to room temperature, added with ice water 13 times the mass of triethoxysilylbutyraldehyde, then added with hydrochloric acid until the pH of the solution was 2, filtered to obtain a filter cake, and then added with deionized water 4 times the mass of the filter cake to obtain a malonic acid reaction solution; (10) Aluminum sulfate and deionized water were mixed in a mass ratio of 1:2.6, and sodium hydroxide was added until the pH of the solution was 10 to obtain an aluminum sulfate solution. The aerogel cable core was placed in a container, and 0.4 times the mass of the aerogel cable core was sprayed with aluminum sulfate solution. After reacting at 160°C for 48 minutes, 0.03 times the mass of the aerogel cable core was sprayed with 8.9% sulfuric acid. After 30kHz ultrasound for 43 minutes, the aerogel cable core was washed with deionized water for 8 times, and dried at 100°C for 13 hours. Then, 0.7 times the mass of the aerogel cable core was sprayed with malonic acid reaction solution, reacted for 7 hours, washed with deionized water for 8 times, and dried at 60°C for 14 hours to obtain a waterproof, impact-resistant and fire-resistant cable.